Hepatitis B virus core antigen has two nuclear localization sequences in the arginine-rich carboxyl terminus. - Eckhardt, S G (1991)
Expression of the hepatitis B virus core antigen (HBcAg) in mouse NIH 3T3 fibroblasts has been shown previously (A. McLachlan et al., J. Virol. 61:683-692, 1987) to result in the nuclear localization of this polypeptide. Since the carboxyl terminus of HBcAg contains four clusters of arginine residues which resemble nuclear localization sequences identified in other nuclear proteins, a series of carboxyl-terminus-truncated HBcAg polypeptides were expressed in mouse fibroblasts to examine the role of these sequences in the cellular localization of HBcAg. By immunofluorescence and cell fractionation analysis, it was demonstrated that regions of the HBcAg polypeptide including the most carboxyl-terminal (cluster 1) and amino-terminal (cluster 4) clusters of arginine residues represent distinct and independent nuclear localization sequences for this polypeptide. Substitution of a threonine residue for the second arginine residue in cluster 4 inactivates the nuclear localization signal in this region of the HBcAg polypeptide, demonstrating the importance of this residue to this signal sequence. However, HBcAg fails to accumulate in the nucleus only when both nuclear localization signal sequences are simultaneously deleted or disrupted by mutation. The possible significance of the nuclear localization sequences identified in the HBcAg polypeptide is discussed in the context of the role of the nucleocapsid in the hepatitis B virus life cycle.